Metropolitan Anthony (Khrapovitsky) between Kant and French spiritualism - Pavel Khondzinskii (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
Today there is no need to prove the importance of I. Kant’s ideas for Russian religious-philosophical thought. A considerable amount of serious recent academic research confirms this obvious truth. At the same time, the field of Russian academic theology is much less developed in this respect, although Kant’s presence in it, both as an opponent demanding an answer from the “theological faculty” and as a source of fruitful ideas, is no less obvious. In particular, Metropolitan Anthony Khrapovitsky’s extramural dialogue with Kant remains unexplored to this day. Meanwhile, as early as in his master’s thesis “Psychological Evidence in favour of Free Will” Anthony devotes an entire chapter to criticism of Kant's “Critiques”, and later, in his articles of the 90s, he addresses Kant’s “Religion within the Bounds of Bare Reason”. This work attracted the attention of Russian theologians more than once. In particular, an answer to Kant’s Christological challenge was already sought by St Innocent of Kherson. Relying by default on his work, however, Metropolitan Anthony concentrates more on an attempt to complete the Kantian idea of moral duty with the idea of love as a divine power that wills and transforms the world. Here he finds unexpected, at first glance, allies in the person of the French spiritualists Ch. Secrétan and A. Fouillée. The latter, in their turn, relied to a considerable extent in their philosophical constructions on French Augustinianism of the 17th century with its ideas of pure or selfless love, ideas that were peculiarly refracted in the autonomous morality of Kant himself. As a result, in the Christological concept of redemptive compassionate love proposed by Metropolitan Anthony, we recognise the ideas of Bl. Augustine, the forefather of Modern philosophy, which have gone through many philosophical iterations.